Cognitive neuroscience, development, and psychopathology : typical and atypical developmental trajectories of attention - Burack, Jacob A.; Enns, James T.; Fox, Nathan A. (New York ; Oxford : Oxford University Press, 2012)
The disciplines of cognitive neuroscience, development, and psychopathology are complementary in the study of human perception and attention. This volume unites scholars sharing common interests in the development of attention and related areas of functioning with different perspectives and methodologies.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Cognitive science; Attention; Psychology, Pathological